2023
DOI: 10.1556/2059.2022.00070
|View full text |Cite
|
Sign up to set email alerts
|

Learning alone together: Emergency-mode educational functions of international virtual exchange in times of the COVID-19 pandemic

Abstract: Virtual exchange practices have been developed at universities for several years; however, the academic importance of VE has grown during the COVID-19 pandemic (Garcés & O'Dowd, 2020; Oswal, Palmer & Koris, 2021). As a result of the restrictions concerning physical mobility, VE has become a ‘first aid kit’ (Reiffenrath, de Louw & Haug, 2020) to continue students' international cooperation. However, at present, there is little research about the nature of students' VE practices during the pandemic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Finally, it is suggested that a broad range of approaches are considered. Here, a relatively simple incorporation of contemporary media was used; however, there are a range of digital collaborative tools that are emerging, particularly following the mass online move prompted by COVID-19 (discussed further in [13,20,36,37]). The use and evaluation of a wider array of tools is worth consideration in further curriculum development.…”
Section: Enhancing the Success Of Future Internationalisation At Home...mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is suggested that a broad range of approaches are considered. Here, a relatively simple incorporation of contemporary media was used; however, there are a range of digital collaborative tools that are emerging, particularly following the mass online move prompted by COVID-19 (discussed further in [13,20,36,37]). The use and evaluation of a wider array of tools is worth consideration in further curriculum development.…”
Section: Enhancing the Success Of Future Internationalisation At Home...mentioning
confidence: 99%
“…Internationalisation abroad can also include the mobility of faculty, projects, programs, and providers. However, internationalisation abroad is not always possible due to either personal circumstance (e.g., socio-economic background), or broader issues (e.g., exchange opportunities are limited at the university; restrictions on travel have been introduced due to a global pandemic) [12,13]. As a result, it has been argued that internationalisation abroad can contribute to perpetuating social disadvantage [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation